Impact of the polycarbonate strippers used in assisted reproduction techniques on embryonic development. Issue 2 (26th November 2020) - Moreau, J; Gatimel, N; Lippi, Y; Tavenier, G; Fauque, P; Guilleman, M; Naylies, C; Huesca, A A; Gayrard, V; Parinaud, J; Leandri, R D
Abstract: STUDY QUESTION: Do daily manipulations of preimplantation embryos with polycarbonate (PC)—made bisphenol A (BPA)—releasing strippers influence embryo development? SUMMARY ANSWER: Compared to glass strippers, PC strippers enhance the blastocyst development rate but this does not seem to be BPA-related. WHAT IS KNOWN ALREADY: PC strippers have been shown to release tiny amounts (around 0.5 ng/ml BPA) of BPA in routine human IVF procedures. A chronic exposure to BPA either in vivo or in vitro during the preimplantation period can impact post-implantation and post-natal development. BPA can act rapidly by binding to membrane receptors and inducing rapid non-genomic effects. STUDY DESIGN, SIZE, DURATION: This experimental study using mouse embryos had a balanced design and blinded evaluations of the endpoints. PARTICIPANTS/MATERIALS, SETTING, METHODS: In vivo fertilized zygotes were obtained from outbred Swiss CD1 mice crossings after an ovarian stimulation. The zygotes were allocated to three daily handling conditions (HCs) and cultured until Day 4 in a single human commercial medium. Each day, the embryos were handled for 20 s either in a PC stripper (HC1) or in a glass stripper (HC2). In HC3, the embryos were pre-exposed to 0.5 ng/ml BPA before being handled for 20 s in a glass stripper. Handling operations were repeated on Days 1, 2 and 3. Embryo development was assessed blindly on Day 4. Expanded blastocysts were selected for a transcriptomic analysis using Agilent Sureprint G3 Mouse GE v2 microarrays and the retrotransposon LINE1- Orf2 expression was analysed using qRT-PCR, as a proxy for a global evaluation of the epigenetic status. MAIN RESULTS AND THE ROLE OF CHANCE: Compared to the embryos manipulated in HC2 (n = 243), those in HC1 (n = 228) developed significantly more often to the blastocyst stage (55 vs 46%; P  <   0.05). It appears the effect of these PC strippers was not BPA-related because embryos pre-exposed to BPA (HC3, n = 230) showed no difference in the blastocyst rate when compared to HC2 (43 vs 46%). When analysing same-stage blastocysts, we noticed no difference in the embryo gene expression between the three HC groups. LARGE SCALE DATA: https://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE148868 . LIMITATIONS, REASONS FOR CAUTION: Our results using a mouse model designed to mimic human conditions (outbred strain, human commercial IVF dishes and a unique commercial human embryonic culture media) are reassuring since no gene was found to be differentially expressed, including LINE-1 genes, as a proxy for a global evaluation of the epigenetic status. However, no global epigenetic analysis of the genome has been performed. Furthermore, we did not evaluate post-implantation events, although BPA exposure during peri-conception could affect foeto-placental and post-natal development. WIDER IMPLICATIONS OF THE FINDINGS: Based on the precautionary principle, several European countries banned the use of BPA in baby bottles and food packaging several years before European Agencies took an official position. The question of applying this principle to plastics in closed contact with human embryos is raised. Further studies are needed for a decision to be made. STUDY FUNDING/COMPETING INTEREST(S): This study was supported by a grant from the Agence de Biomédecine (AOR 2016). The authors declare no competing interest.